REFORMULASI HUKUM TENTANG HAK GUGAT BAGI PEMEGANG SAHAM DIBAWAH 1/10 - Ansory, Wachid Aditya; Nasution, Krisnadi (Jurnal Hukum Bisnis Bonum Commune, 2022)
This journal is entitled "Legal Reformulation of Actions Right Against Under 1/10 Shareholders”. The method of approach used in this study is normative legal research, which is a study that mainly studies the rule of law, principles of law, and legal theory/doctrine. This research was also conducted using the statutory approach and the conceptual approach, which is related to the responsibility of the Director against Limited Liability Company Loss caused by the Director Fault and legal protection of Under 1/10 Shareholders Against Loss of Limited Liability Company Caused by The Director Fault.